Allergic Rhinitis - Ni Luh Eka Damayanti (Jurnal KESANS : Kesehatan dan Sains, 2023)
Allergic rhinitis (AR) is a common chronic illness worldwide, characterized by immunoglobulin E (IgE)-mediated reactions to inhaled allergens. Allergic rhinitis (AR) frequently presents alongside asthma and conjunctivitis, and it is a significant global health issue that imposes a substantial burden and handicap on a global scale. The classification of Allergic Rhinitis (AR) into intermittent or chronic and mild or moderate/severe was established by the Allergic Rhinitis and its Impact on Asthma (ARIA) program. The diagnosis is established through a comprehensive assessment of the patient's clinical history, thorough physical examination, and appropriate diagnostic tests. The pharmacological treatments most commonly employed consist of oral, intranasal, or ocular H1-antihistamines, intranasal corticosteroids, or a set combination of intranasal H1-antihistamines and corticosteroids.